Progression of brain atrophy in PSP and CBS over 6 months and 1 year. (8th November 2016) - Dutt, Shubir; Binney, Richard J.; Heuer, Hilary W.; Luong, Phi; Attygalle, Suneth; Bhatt, Priyanka; Marx, Gabe A.; Elofson, Jonathan; Tartaglia, Maria C.; Litvan, Irene; McGinnis, Scott M.; Dickerson, Bradford C.; et al.
Abstract : Objective: To examine the utility and reliability of volumetric MRI in measuring disease progression in the 4 repeat tauopathies, progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS), to support clinical development of new tau-directed therapeutic agents. Methods: Six- and 12-month changes in regional MRI volumes and PSP Rating Scale scores were examined in 55 patients with PSP and 33 patients with CBS (78% amyloid PET negative) compared to 30 normal controls from a multicenter natural history study. Longitudinal voxel-based morphometric analyses identified patterns of volume loss, and region-of-interest analyses examined rates of volume loss in brainstem (midbrain, pons, superior cerebellar peduncle), cortical, and subcortical regions based on previously validated atlases. Results were compared to those in a replication cohort of 226 patients with PSP with MRI data from the AL-108-231 clinical trial. Results: Patients with CBS exhibited greater baseline atrophy and greater longitudinal atrophy rates in cortical and basal ganglia regions than patients with PSP; however, midbrain and pontine atrophy rates were similar. Voxel-wise analyses showed distinct patterns of regional longitudinal atrophy in each group as compared to normal controls. The midbrain/pons volumetric ratio differed between diagnoses but remained stable over time. In both patient groups, brainstem atrophy rates were correlated with disease progression measured using the PSP Rating Scale. Conclusions: Volume loss is quantifiable over a period of 6 months in CBS and PSP. Future clinical trials may be able to combine CBS and PSP to measure therapeutic effects.